How does Unified Theory of Acceptance and Use of Technology (UTAUT) Work on Adopting Financial Technology (FinTech) by MSMEs? - Wismantoro, Yohan; Susilowati, MG Westri Kekalih Susilowati (Universitas Dian Nuswantoro Semarang, 2021)
Micro Small and Medium Enterprises (MSMEs) have a very significant role in the economy, can even be said to be the backbone of the economy. However, MSMEs are precisely the sector hardest hit by the Covid-19 pandemic. Digitalization creates new opportunities for MSMEs in the pandemic. FinTech, one of the implementations of digitalization should be pursued to be used by MSMEs. Using path analysis processed using Partial Least Square (PLS), this research aims to identify how Unified Theory of Acceptance and Use of Technology (UTAUT) works on Adopting FinTech by MSMEs. The Outer Model and Inner Model reflect that the model work. The outer loading value of ? 0.7, AVE value ? of 0.5, Cronbach's Alpha ? 0,70, a correlation value ? of 0.50; and Composite Reliability ? 0.6, and R-Square 0.716 reflect it. However, regarding the factors that influence intention to use, it is different from previous research that became a reference. There are only four hypotheses proven. Those are Context had a significant positive effect on Perceived Ease of Use and Perceived Usefulness, and Perceived Ease of Use and Perceived Usefulness had a significant positive effect on the intention to use fintech. Keywords: FinTech, MSMEs, Digitalization, UTAUT, Inclusive